2022
DOI: 10.1177/15562646221078415
|View full text |Cite
|
Sign up to set email alerts
|

It’s Almost as if Stakeholder Engagement is the Annoying ‘Have-to-do'…”: Can Ethics Review Help Address the “3 Ts” of Tokenism, Toxicity, and Tailoring in Stakeholder Engagement?

Abstract: Ethics guidance recommends that researchers engage stakeholders and that RECs review research for such engagement. The ethics review process may present a unique opportunity to support stakeholder engagement practices for HIV prevention studies. We conducted 28 interviews with experts from 12 countries to explore this issue, and analyzed the data using Thematic Analysis. We found that the value of engagement and review processes was strongly endorsed. However, we identified 3 major thematic complexities, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The comment also suggests that the RECs in question are perceived as far removed from the communities whose best interests they are required to protect, inviting further reflection on the role of the required layperson on every REC as prescribed by national guidance (DoH, 2015). The experienced relationship between RECs, researchers, and research communities is currently enjoying critical study (Wilkinson et al, 2021; 2022) which warrants further consideration and exploration in future empirical studies.…”
Section: The Role Of Recsmentioning
confidence: 99%
See 4 more Smart Citations
“…The comment also suggests that the RECs in question are perceived as far removed from the communities whose best interests they are required to protect, inviting further reflection on the role of the required layperson on every REC as prescribed by national guidance (DoH, 2015). The experienced relationship between RECs, researchers, and research communities is currently enjoying critical study (Wilkinson et al, 2021; 2022) which warrants further consideration and exploration in future empirical studies.…”
Section: The Role Of Recsmentioning
confidence: 99%
“…What the authors argue well is that they have an expectation of the need for change because, by RECs and researchers uncritically pursuing universal, arguably western-oriented ethics principles, they inadvertently promote the dominant worldview of some researchers, while showing disrespect for alternative world views. The change requested is that researchers, through engagement with their research communities should have the ethical right to argue for the naming of a research site/community if this is found to be appropriate after appropriate community engagement (Wilkinson et al, 2022). Here, we again raise the issue of the ethical standard of anonymity as applied by the specific RECs that Nduna et al (2022) refer to and which are described as if all RECs in South Africa subscribe to site anonymity without exception.…”
Section: The Authors’ Identity and Worldviewmentioning
confidence: 99%
See 3 more Smart Citations